Eco-Friendly Solar Refrigerator: Peltier Cooling, Remote Monitoring for Sustainable and Efficient Energy Consumption - Putri Puspita, Nabilla; Yusfi, Meqorry; Rasyid, Rahmat (Jurusan Fisika FMIPA Universitas Andalas, 2025)
Electricity is essential for everyday needs, including food preservation through refrigeration. However, access to electricity remains uneven in remote regions due to geographical constraints. Solar energy offers a promising alternative, especially in areas with abundant sunlight, highlighting the need for compact, portable, and eco-friendly cooling system. This study aims to design an eco-friendly cooling system using the Seebeck Effect in Peltier TEC 12706 modules powered by solar energy. The system consists of two Peltier TEC 12706 modules, a 50 Wp solar panel, and a 33 Ah accumulator, with a cooling chamber measuring 26 × 17 × 10 cm. Temperature and humidity were remotely monitored via the Blynk application. Experimental results showed the lowest temperature achieved was 15°C between 08:00 AM and 10:00 AM. In comparison, the most significant temperature drop of 11.7°C occurred between 12:00 PM and 02:00 PM, with an average light intensity of 176,846.15 Lux. Although the system demonstrated cooling performance, the minimum temperature of 15°C does not meet the standard refrigeration temperature of around 0°C. Therefore, the current system is not yet suitable for replacing conventional refrigerators, but it shows potential as an environmentally friendly alternative cooling solution with further development.